Adjuvant androgen deprivation therapy for poor-risk, androgen receptor–positive salivary duct carcinoma. (March 2019) - van Boxtel, W.; Locati, L.D.; van Engen-van Grunsven, A.C.H.; Bergamini, C.; Jonker, M.A.; Fiets, E.; Cavalieri, S.; Tooten, S.; Bos, E.; Quattrone, P.; Verhaegh, G.W.; Schalken, J.A.; et al.
Abstract: Aim: Salivary duct carcinoma (SDC), an aggressive subtype of salivary gland cancer, is androgen receptor (AR)–positive in 67–96% of cases. In patients with locally recurrent and metastatic (R/M) AR-positive SDC, androgen deprivation therapy (ADT) has an overall response rate of 18–64.7%. In this study, we describe the efficacy of adjuvant ADT in patients with poor-risk (stage 4a) AR-positive SDC. Methods: This is a retrospective cohort study in which patients with stage 4a AR-positive SDC were offered adjuvant ADT, i.e. bicalutamide, luteinizing hormone-releasing hormone (LHRH) analogue or a combination of these after tumour resection. In the control group, data were collected on patients with stage 4a SDC who underwent a tumour resection but did not receive adjuvant ADT. Results: Twenty-two AR-positive SDC patients were treated with adjuvant ADT for a median duration of 12 months. The control group consisted of 111 SDC patients. After a median follow-up of 20 months in the ADT-treated patients and 26 months in the control group, the 3-year disease-free survival (DFS) was estimated as 48.2% (95% confidence interval [CI] 14.0–82.4%) and 27.7% (95% CI 18.5–36.9%) ( P  = 0.037). Multivariable Cox regression analysis showed a hazard ratio of 0.138 (95% CI 0.025–0.751, P  = 0.022) for DFS and 0.064 (95% CI 0.005–0.764, P  = 0.030) for overall survival (OS) in favour of the ADT-treated patients. Conclusion: Poor-risk, AR-positive SDC patients who received adjuvant ADT have a significantly longer DFS compared with patients in the control group, who did not receive adjuvant ADT. For OS, this was just below and above the significance level, in case there was or was no correction for confounders. Highlights: Salivary duct carcinoma (SDC) is an aggressive subtype of salivary gland cancer. Palliative androgen deprivation therapy (ADT) has a response rate of 18–64.7%. In this retrospective cohort study, we describe the efficacy of adjuvant ADT in poor-risk SDC. Adjuvant ADT showed a significantly longer disease-free survival. Overall survival was significantly longer after correction for confounders.